Solusi dalam Manajemen Keuangan Pendidikan di RA Nurul Huda - Allisyanina Yustie Salsabilla; Nafrisa Alliyah Putri Sochib; Bintang Septa Aulia; Albarrotu’ Thadqiyah Arbaniyah; M. Naufal Dzakiy Mu’afiy (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research is used to examine the state of financial management in an institution. By using the principal of RA Nurul Huda as our resource person to find out more in-depth information about financial management in the institution, and what attitude the principal takes in dealing with financial management in the educational institution. From the results of this research, it is known that the RA Nurul Huda institution reports the results of real income and expenditure of funds on a regular basis every month. And the school has also prepared funds for several students if they need them one day.